PRESERVING PROVERBS IN THE DIGITAL AGE: A QUALITATIVE STUDY ON STAKEHOLDER PERCEPTIONS OF ARTIFICIAL INTELLIGENCE FOR ACEHNESE LANGUAGE HERITAGE - Hajar, Ibnu; Husna, Asmaul; Aulia, Muhammad Kahfi; Muntazar, T. (Journal Informatic, Education and Management (JIEM), 2026)
This qualitative study investigates the perceived opportunities and challenges of developing an artificial intelligence (AI) application for preserving Acehnese proverbs (Hadih Maja), a critical yet endangered component of cultural heritage. Conducted as a multi-stakeholder feasibility study, it engages academics (linguists, anthropologists, AI/data scientists) and cultural custodians (tokoh adat) in North Aceh and Lhokseumawe, Indonesia. Through reflexive thematic analysis of in-depth interviews, the research reveals a dualistic landscape. Stakeholders recognize AI’s transformative potential as a bridge for intergenerational engagement, enabling interactive, mobile-based learning for youth. However, this promise is counterbalanced by formidable socio-technical hurdles. Key challenges include the fundamental "low-resource" paradox—where data scarcity severely limits natural language processing capabilities—and profound ethical risks of cultural decontextualization, trivialization, and the erosion of community sovereignty over knowledge. The findings underscore that the primary impediments are not merely technical but deeply socio-technical, necessitating an approach that makes community governance and cultural integrity foundational. The study concludes that a successful initiative must be reconceptualized from an "AI development project" to a "community-led cultural revitalization project enabled by AI," prioritizing participatory co-design, ethical data governance guided by the CARE principles, and the creation of a culturally-grounded multimodal corpus before any substantial technical development. This research offers a critical framework for ethically and effectively leveraging AI in endangered language contexts globally.